2016
DOI: 10.1016/j.jneumeth.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon imaging of chronically implanted neural electrodes: Sealing methods and new insights

Abstract: Background Two-photon microscopy has enabled the visualization of dynamic tissue changes to injury and disease in vivo. While this technique has provided powerful new information, in vivo two-photon chronic imaging around tethered cortical implants, such as microelectrodes or neural probes, present unique challenges. New Method A number of strategies are described to prepare a cranial window to longitudinally observe the impact of neural probes on brain tissue and vasculature for up to 3 months. Results It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 59 publications
5
113
0
Order By: Relevance
“…Astroglial reactivity around the implant leads to increased expression of connexon-43 (Cx43), an astroglial hemichannel and gap junction known to facilitate the spread of inflammation 3133 . In turn, inflammation leads to the recruitment of blood-borne monocytes and neutrophils through the intact BBB, and to the formation of multinucleated giant cells 34 . In addition, this inflammation alters the expression level of matrix metalloproteinases, together leading to further breakdown of the BBB and facilitating the influx of blood-serum proteins, red blood cells and leukocytes 26 .…”
Section: Astrocytic Responses To Device Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astroglial reactivity around the implant leads to increased expression of connexon-43 (Cx43), an astroglial hemichannel and gap junction known to facilitate the spread of inflammation 3133 . In turn, inflammation leads to the recruitment of blood-borne monocytes and neutrophils through the intact BBB, and to the formation of multinucleated giant cells 34 . In addition, this inflammation alters the expression level of matrix metalloproteinases, together leading to further breakdown of the BBB and facilitating the influx of blood-serum proteins, red blood cells and leukocytes 26 .…”
Section: Astrocytic Responses To Device Insertionmentioning
confidence: 99%
“…Pericytes and NG2-glia have also gained recent attention because of their suggested reparative potential following injury 222226 . Also, blood-borne myeloid cells (such as monocytes and leukocytes) can infiltrate on BBB disruption, and their involvements around devices have been investigated and discussed elsewhere 34,36 . The foreign-body response to neural implants has been comprehensively discussed in refs 26,35,156 .…”
Section: Figmentioning
confidence: 99%
“…It would be highly desirable to chronically record from the same neuronal population using implanted electrodes together with different chronic Ca 2+ imaging techniques. While certainly challenging, a recent study demonstrated that this should be technically feasible [93]. Without further quantification of the measurement idiosyncrasies of different recording techniques, relative measures of variability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To catch cellular and vascular dynamics, and correlates changes of tissue characteristics to recording performance in real time, various in vivo live imaging approaches have been developed. Two-photon microscopy (TPM) has been used to visualize vascular damage and remodeling, microglial polarization and migration [48, 49], or shape and activity of the neurons around electrode devices [20, 50] before and after electrode array insertion and over extended periods of time. Compared to technologies like MRI and microCT, multi-photon microscopy offers high spatial resolution for resolving cellular processes, sufficient temporal resolution for tracking calcium activity, and ample cell type specific labeling (Capabilities of various imaging modality is summarized in Table 2).…”
Section: Methodology Development For Characterizing the Interfacementioning
confidence: 99%